Intervention of ICTs in Rice Production in Bangladesh: An Impact Study - Das, S; Munshi, MNU; Kabir, W; Biswas, JK (Bangladesh Rice Journal, 2017)
Research led productivity gain in rice has enabled the growth of rice production. Organized research and extension played a great role in the success of rice development in the country. However, there exists scope for further yield gain through minimizing gap between research and farm. Information Communication Technology (ICT) has proved to be significant to enhance agricultural production. Realizing its potential, Bangladesh has currently started using ICT for its agricultural development programmes. The study has revealed the strong relationship of rice production of the ICT farmers with that of non-ICT ones. DiD (Difference in Differences) model was used to analyze the comparison of rice production of two service areas. Recall method was used to collect the data. The result indicates that the production of Boro and T. Aman rice from ICT service areas has increased more than those of non-ICT areas. The counter factual outcome of DiD analysis reflects the perspective weaker treatment of non-ICT service area and stronger one of the ICT service area. Bangladesh Rice j. 2016, 20(2): 67-72